The University of Genova Climate Policies - Federico Delfino; Michela Gallo; Paola Laiolo; Valentina Marin; Stefano Spotorno; Adriana Del Borghi (Universitas Diponegoro, 2025)
The University of Genova (UniGe) has undertaken a significant commitment against climate change, with the goal of becoming climate neutral by 2030. The commitment began in 2014 with the calculation of its carbon footprint and has developed through several stages. In 2019, it joined